Pengaruh Faktor Psikologi Konsumen dan Online Store Environment Terhadap Purchase intention Pada E-commerce Model Bisnis C2C - Bambang Eko Samiono (Asian Journal of Innovation and Entrepreneurship, 2018)
The existence of the internet has put e-commerce on the concept of one stop shopping. Online trends provide a variety of ease in accessing and running a business with e-commerce. E-commerce C2C model is one of the most vibrant business models in e-commerce. Here business owner are required to be sensitive to the factors that affect consumers to purchase intention on online store. This study examines the influence of internal factors of the Online Store Environment (web quality and web brand) and external factors of consumer psychological factors (personality based, perception based and experience) on purchase intention of e-commerce C2C model through online trust mediator. In the category of e-commerce C2C model is represented by Bukalapak, Tokopedia, OLX and FJB Kaskus. The target sample is the respondents who in the last three months visited one of the e-commerce sites in the south of Jakarta with a total sampling of 100 respondents. Data processing is used with path analysis method. The results show that the e-commerce C2C purchase intention model is influenced by online store environment factor (web quality) either directly or indirectly through online trust mediation. The consumer psychological factor (personality based) affects the purchase intension directly while experience indirectly affects purchase intention through online trust